Are cognitive "insomnia" processes involved in the development and maintenance of delayed sleep wake phase disorder?. (April 2016) - Richardson, Cele E.; Gradisar, Michael; Barbero, Sebastian C.
Summary: Although individuals with delayed sleep wake phase disorder (DSWPD) and chronic insomnia disorder (CID) share many of the same phenomenological experiences, theories relating to the development and maintenance of these disorders are distinct in focus. Unlike CID, theory relating to DSWPD is primarily physiologically based and assumes almost no cognitive pathway. However, recent research findings suggest that individuals with DSWPD also display many of the sleep-disordered cognitive processes that were previously assumed to be unique to the insomnia experience. As such, this review aims to summarise current research findings to address the question "Could cognitive processes be involved in the development and maintenance of DSWPD?" In particular, the presence of cognitive and physiological pre-sleep arousal, sleep-related attentional bias, distorted perception of sleep and daytime functioning, dysfunctional beliefs and safety behaviours will be investigated. As this emerging area of research requires a stronger evidence base, we highlight suggestions for future investigation and provide preliminary practice points for clinicians assessing and treating "insomnia" in patients with DSWPD.